Penerapan Denda Pada Jual Beli Taqsith Perspektif Hukum Islam: (Studi Kasus Di Toko Ibu Novi Desa Ciluluk Kecamatan Cikancung) - SitiHalimah, Lina; Wibawa , Ginan (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
Buying and selling on credit is easier than using cash because you can get what you need, when you can't buy in cash, as is the case with the people in Ciluluk Village who do this common thing. With this convenience, sometimes the buyer makes a mistake, namely being late in paying the installments, so the seller imposes a fine on the buyer, but the fine is not notified to the buyer at the time of the contract. This research aims to determine the implementation of credit buying and selling (taqsith) with a fine system at the Ibu Novi Shop, Ciluluk Village, Cikancung District and to find out the perspective of Islamic law on the application of credit buying and selling fines (taqsith) at the Mrs Novi Shop, Ciluluk Village, Cikancung District. This research is a type of empirical normative research with a descriptive qualitative approach, with data collection using observation, interviews and documentation. The results of this research are that in practice, the sale and purchase of credit (taqsith) is considered to be damaged (facade) in the contract, because there are fines that are not disclosed at the time of the contract. According to Islamic law, the law of buying and selling credit (taqsith) at Mrs. Novi's shop in Ciluluk Village is invalid because it violates the rules of Islamic law, where the fine is applied suddenly and the funds from the fine are not intended for social funds.